2007
DOI: 10.1088/0264-9381/24/16/006
|View full text |Cite
|
Sign up to set email alerts
|

Testing outer boundary treatments for the Einstein equations

Abstract: Various methods of treating outer boundaries in numerical relativity are compared using a simple test problem: a Schwarzschild black hole with an outgoing gravitational wave perturbation. Numerical solutions computed using different boundary treatments are compared to a 'reference' numerical solution obtained by placing the outer boundary at a very large radius. For each boundary treatment, the full solutions including constraint violations and extracted gravitational waves are compared to those of the referen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
179
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(179 citation statements)
references
References 63 publications
(266 reference statements)
0
179
0
Order By: Relevance
“…Quasi-equilibrium [28,29] initial data are constructed [30] to solve the Einstein constraint equations [31] for binaries with low (∼10 −4 ) eccentricity [32][33][34] and are evolved using a generalized harmonic formulation [35][36][37][38] of Einstein's equations and damped harmonic gauge [39][40][41]. The adaptively-refined [42] grid extends from pure-outflow excision boundaries conforming to the shapes of the apparent horizons [24,41,43,44] to an artificial outer boundary where constraintpreserving boundary conditions [38,45,46] are imposed. After merger, the grid has only a single excision boundary [24,43].…”
Section: Techniquesmentioning
confidence: 99%
“…Quasi-equilibrium [28,29] initial data are constructed [30] to solve the Einstein constraint equations [31] for binaries with low (∼10 −4 ) eccentricity [32][33][34] and are evolved using a generalized harmonic formulation [35][36][37][38] of Einstein's equations and damped harmonic gauge [39][40][41]. The adaptively-refined [42] grid extends from pure-outflow excision boundaries conforming to the shapes of the apparent horizons [24,41,43,44] to an artificial outer boundary where constraintpreserving boundary conditions [38,45,46] are imposed. After merger, the grid has only a single excision boundary [24,43].…”
Section: Techniquesmentioning
confidence: 99%
“…For the outer boundaries, we implement Sommerfeld boundary conditions and follow the prescription given in [48]. We have also used maximally dissipative boundary conditions, but found that they led to larger reflections at the boundaries which, in turn, corrupt the waveform extraction at late times.…”
Section: Einstein Equationsmentioning
confidence: 99%
“…This principle was used in [10] to assess the numerical performance of various boundary conditions. First, a reference solution is computed on a very large computational domain.…”
Section: Numerical Testsmentioning
confidence: 99%
“…Finally, the solution on the smaller domain is compared with the reference solution, measuring the spurious reflections and constraint violations caused by the boundary conditions. Here we use the same test problem as in [10]. The initial data are taken to be a Schwarzschild black hole of mass M in Kerr-Schild coordinates with an outgoing odd-parity quadrupolar gravitational wave perturbation (satisfying the full nonlinear constraint equations).…”
Section: Numerical Testsmentioning
confidence: 99%
See 1 more Smart Citation